Mallampatti Score as a Predictor for Risk of Obstructive Sleep Apnea (Medical Forum Monthly, 2024)
Objective: To observe the association of high Mallampatti score with obstructive sleep apnea and to see its predictive value for high risk individuals.Study Design: A Prospective Cross Sectional Study.Place and Duration of Study: This study was conducted at the Department of Anaesthesia Bahawal Victoria Hospital Bahawalpur, from July, 2017 to January, 2018.Materials and Methods: Body mass index was calculated from weight and height. Mallampatti score was evaluated besides Berlin questionnaire, snoring, Epworth sleeping scale. Patients were divided into four groups on the basis of Mallampatti score. Mallampatti score was cross tabulated against snoring grades, Berlin score risk, Epworth score classes and body mass index categories and was compared by applying Chi-square test. SPSS v.23 was used, considering p≤0.05 statistically significant.Results: In group III and IV of Mallampatti score, there was significantly more snoring of grade III and grade IV (p=0.043). Mallampatti score difference was not statistically significant among normal, overweight and obese persons (p=0.962). On the basis of Berlin Score risk, the difference was not found to be of any statistical significance (p=0.366). There was a statistically significant increase in Mallampatti score when we moves from class I to class IV of Epworth Sleep Score (p=0.031).Conclusion: We concluded that high Mallampatti score is greatly interrelated with snoring and high Epworth sleep score. This shows a strong relationship between high Mallampatti score and obstructive sleep apnea. Therefore, Mallampatti score can be used to predict the risk of obstructive sleep apnea.